2005
DOI: 10.1002/cbm.35
|View full text |Cite
|
Sign up to set email alerts
|

Using the SWAP-200 in a personality-disordered forensic population: is it valid, reliable and useful?

Abstract: Although the small sample size allows only preliminary conclusions about the validity of this instrument, early results show a reduction of the diagnosis of comorbidity compared with the SCID-II, together with an increased number of expected associations between independent measures of interpersonal functioning and categories of personality disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 28 publications
2
40
0
1
Order By: Relevance
“…In a sample of 24 outpatients, personality syndromes calculated from independent interviewer ratings had a median correlation of 0.80 with the same SWAP dimensions calculated from the treating clinicians' assessments of the patients [24,25]. In other research, in a sample of 90 inpatients, 12 SWAP-based personality disorder scales derived from researchers' ratings of attachment interviews and chart records correlated highly with the interpersonal circumplex ratings of patients' personalities provided by their nurses [26,27]. In a study of 47 outpatients [28], SWAP dimensions of borderline, antisocial, and obsessive-compulsive personality disorders based on ratings by the treating clinicians showed a strong pattern of concurrent and discriminant validity with relevant dimensions of the Personality Assessment Inventory [29], a self-report measure of personality pathology completed by the patients.…”
Section: Methodsmentioning
confidence: 99%
“…In a sample of 24 outpatients, personality syndromes calculated from independent interviewer ratings had a median correlation of 0.80 with the same SWAP dimensions calculated from the treating clinicians' assessments of the patients [24,25]. In other research, in a sample of 90 inpatients, 12 SWAP-based personality disorder scales derived from researchers' ratings of attachment interviews and chart records correlated highly with the interpersonal circumplex ratings of patients' personalities provided by their nurses [26,27]. In a study of 47 outpatients [28], SWAP dimensions of borderline, antisocial, and obsessive-compulsive personality disorders based on ratings by the treating clinicians showed a strong pattern of concurrent and discriminant validity with relevant dimensions of the Personality Assessment Inventory [29], a self-report measure of personality pathology completed by the patients.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the 12-factor solution's "dissociation" dimension does not appear elsewhere; "histrionic sexualization" in the 11-and 12-factor solutions may map onto the DSM and/or factoranalytic histrionic diagnoses, but these empirical relations are not reported. Although a few small-sample studies have reported promising results with the seven factors (Diener & Hilsenroth 2004) or DSM prototypes (Martin-Avellan et al 2005), additional studies of the 12 factors have not been reported. Accordingly, whether the SWAP-200 structure is robust or relatively sampledependent, or why different structures have emerged, is unknown.…”
Section: Alternative Conceptualizationsmentioning
confidence: 99%
“…The preliminary results of a small sample study (n = 30) of forensic PD patients detained in high security conducted by the current authors were promising in terms of the SWAP-200 offering a more parsimonious classification of DSM PD categories compared with the SCID-II and improving the convergent validity of the PD categories when both SWAP-200 and SCID-II were assessed against other instruments assessing interpersonal functioning and attachment (Marin-Avellan, McGauley, Campbell, & Fonagy, 2005). It seems important to investigate whether the SWAP-200 Antisocial PD category can be useful in differentiating forensic psychiatric patients in a way that is both clinically meaningful and efficient at predicting violence, unlike the DSM diagnosis of Antisocial PD.…”
mentioning
confidence: 83%